Students’ Introvert/Extrovert Writing Abilities On Descriptive Text: Is Writing Easier For Introverts? - Manurung, Lastri Wahyuni; Saragi, Christina Natalina; Silalahi, Dewi Paulina; Hasani, Elsya Elita Merlyn (Jurnal Ilmu Sosial Mamangan, 2025)
This study examines the Writing Ability of Introvert/Extrovert Students in Descriptive Text: Is Writing Easier for Introverts? Based on DiTiberio's statement (1989), the difference between extrovert and introvert individuals lies in the way of decision making, where extrovert individuals tend to be more objective and structured, while introvert individuals are more subjective and value personal values. The findings of the study indicate that students with introverted traits have better achievement in descriptive writing than extrovert students, with an average score of 74.27. This study emphasizes the importance of considering students' personal traits in determining the right teaching techniques to improve learning outcomes. The Writing Ability of Introvert/Extrovert Students in Descriptive Text becomes easier for introverts.